PENGANGKATAN TENAGA HONORER DI KABUPATEN BELU DITINJAU DARI PERATURAN PEMERINTAH NOMOR 43 TAHUN 2007 TENTANG PERUBAHAN PERATURAN PEMERINTAH NOMOR 48 TAHUN 2005 TENTANG PENGANGKATAN TENAGA HONORER MENJADI CALON PEGAWAI NEGERI SIPIL - Sulun, Esebius; Yohanes, Saryono; Ratu Udju, Hernimus (Petitum Law Journal, 2023)
The appointment of Honorary Staff is the government's effort to improve the quality of education and welfare, but in its implementation there needs to be evaluation for further program improvements. This article aims to find out how the appointment of honorary staff as civil servant candidates at the Belu Regency Regional Civil Service Agency is viewed from Government Regulation Number 43 of 2007 concerning Amendments to Government Regulation Number 48 of 2005 concerning the Appointment of Honorary Personnel to become Civil Servant Candidates, and aims to find out an overview of the application of good governance principles in the appointment of honorary staff in the Belu Regency Government area. This research uses empirical legal methods, namely methods that function to see law in real terms and examine how law works in the community environment. Based on the research results, the author obtained an answer to the existing problem, that the implementation of Government Regulation Number 43 of 2007 concerning Amendments to Government Regulation Number 48 of 2005 concerning the Appointment of Honorary Personnel as civil servant candidates by the Regional Civil Service Agency of the Belu Regency Government is not optimal, there are still employees honorary employees who have served for a long time but have not yet been appointed as civil servants. Another factor is the lack of good communication between the government and the community regarding information, financing needs, recruitment procedures, selection procedures, determination of graduation and announcement of graduation. Based on these factors, it is hoped that the Belu Regency Government, through the Regional Civil Service Agency, will carry out outreach regarding procedures and information.